Inversión en la infancia de América Latina y el Caribe = Investing in children in Latin America and the Caribbean (Bogotá, Colombia : Ediciones Gráficas, 2000)
Giving children a good start and good opportunities in life is not only a moral imperative but an internationally recognised right under the Convention on the Rights of the Child.
Dar a los niños un buen comienzo y buenas oportunidades en la vida no es solamente un imperativo moral sino un derecho reconocido internacionalmente en virtud de la Convención sobre los Derechos del Niño.
TABLE OF CONTENTS Overview Fundamental Children's Rights: Survival, Development, Protection and Participation Modest Progress: The Gains of the 19905 The Continuing Toll of Poverty Investing in Children: Beneficial and Cost-Effective and other more...
Keywords: DERECHO DEL NIÑO; INFANCIA -- BIENESTAR; NIÑOS LEGISLACIÓN